A Short Review on Heterocyclic Compounds Showing Anti-Breast Cancer Activity - Ayana, R.; Vijayakumar, B.; Athulya, P.; Anjana, V. S.; Vismaya, K. V.; Swarnalatha, G. (Journal of Scientific Research, 2021)
Breast cancer (BC) is the most common cancer for females, and its incidence tends to increase year by year. Currently, the backbone of therapy for BC is mainly chemotherapy; however, its toxicity in normal cells and acquired tumor resistance to the drug users are considered the main barriers. Therefore, there is still an urgent need for the development of more effective and safer anti-BC agents. Based on previous reference documents in recent years, this review covers the work reported on the anti-BC compounds classified according to the structures. This review summarized significant anti-BC compounds organized by functional groups according to the animal model data, although there would be some limitations. This review highlights the properties of new compounds having promising anti-BC properties, which may be proven to be more effective and selective, and possibly free of unwanted side effects. The reviewed compounds represent an interesting possibility of overcoming BC and reducing the percentage of patients with an inadequate response to drug therapy.